Penerimaan Diri pada Remaja Panti Asuhan Puteri Aisyiyah Medan - Patrick Funaidi; Airin; Angel; Angela; Sri Hartini (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this research is to see a picture of self-acceptance in adolescent orphanages. The source of this research consisted of five research subjects who were young women at Puteri Aisyiyah Medan Orphanage and three informants. The procedure for taking the subject uses purposive sampling technique. The research data were collected using observation and interview methods. The results obtained are that young women at Puteri Aisyiyah Orphanage have a good self-acceptance picture, and can accept themselves with their status as children of an orphanage.